Simulation study of phosphorus remediation using lanthanum chloride-modified fly ash and Mg-O modified biochar at the sediment water interface - Ji, Minghao; Men, Zhigao; Zhang, Jihua; Tian, Ao; Wang, Jiayi; Sun, Xiaoyu; Yang, Chengnian; Cheng, Shuailong; Wang, Yijie; Chen, Wenlong; Gao, Zilan; Chai, Beibei (SPIE, 2024)
Water eutrophication is a significant environmental governance challenge faced by the world today, with nutrient overloading being a primary cause, while aquatic sediment serves as the main storage site for these nutrients and other pollutants. This study focused on the Guangfu Ancient City Moat in Handan City as the research subject, where lanthanum-modified fly ash microspheres and Mg-O modified biochar, independently developed and processed, were employed in an in-situ remediation efficiency simulation within containment boxes. The study also investigated phosphorus recovery and utilization. The removal rates of total phosphorus in the containment boxes with fly ash microspheres, biochar, fly ash microspheres wrapped in non-woven fabric, and biochar wrapped in non-woven fabric were 51.91%, 66.67%, 84.52%, and 84.14% respectively, with removal effectiveness ranking as NO. 4’ NO. 4” > NO. 3 NO. 2. The research indicated that both biochar and fly ash microspheres displayed outstanding performance in phosphorus adsorption, with fly ash microspheres being more cost-effective compared to activated carbon. The containment box experiments effectively demonstrated the significant impact of fly ash microspheres in the efficient recovery of phosphorus resources and the improvement of aquatic environments, offering essential insights for the integrated management of water quality and soil.